1998
DOI: 10.1136/jnnp.65.5.767
|View full text |Cite
|
Sign up to set email alerts
|

Pallidal activity during dystonia: somatosensory reorganisation and changes with severity

Abstract: A woman with progressive, medically intractable right upper limb dystonia underwent a pallidotomy with only transient improvement. During the procedure her dystonia became more severe as she repeatedly made a fist to command in order to provoke dystonia transiently (movement provoked dystonia). Comparisons within cells in the internal segment of the globus pallidus (Gpi) disclosed that the firing rate was the same at rest, with making a fist, and during movement provoked dystonia. However, the firing rate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
98
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(107 citation statements)
references
References 11 publications
9
98
0
Order By: Relevance
“…GPi firing rates(as well as GPe) are reduced in dystonic patients as compared to Parkinson's disease patients or parkinsonian primates, but slightly faster than reported in patients with hemiballismus 13,20,40,41 . Pallidal activity also seems to correlate inversely with dystonia severity 42 . No human data on normal firing rates are available for comparison.…”
Section: Discussionmentioning
confidence: 95%
“…GPi firing rates(as well as GPe) are reduced in dystonic patients as compared to Parkinson's disease patients or parkinsonian primates, but slightly faster than reported in patients with hemiballismus 13,20,40,41 . Pallidal activity also seems to correlate inversely with dystonia severity 42 . No human data on normal firing rates are available for comparison.…”
Section: Discussionmentioning
confidence: 95%
“…During movement, most of these neurons were activated, whereas the activation-to-inactivation ratio was reversed for nonparkinsonian monkeys. 99 In dystonia, experimental recordings showed enlarged receptive fields of dystonic joints in the somatosensory cortex, 100 thalamus, 101 and globus pallidus 102,103 (but also see the 2003 article by Hutchison et al 104 ).…”
Section: Effects On Coactivation Of Competing Motor Programsmentioning
confidence: 98%
“…Based on pharmacologic studies, there seems to be a relative increase in the activity of striatal neurons of the direct pathway over those that give rise to the indirect pathway in dystonia [195,196], and single-cell recording studies in patients undergoing functional neurosurgical treatments have demonstrated low discharge rates in both GPe and GPi [197][198][199][200][201][202], in distinction to the aforementioned changes in PD where GPi discharge rates are generally increased. The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204].…”
Section: Dystoniamentioning
confidence: 99%